Diverse Autonomic Nervous System Stress Response Patterns in Childhood Sensory Modulation - Christensen, Jacquelyn S.; Wild, Heather; Kenzie, Erin S.; Wakeland, Wayne; Budding, Deborah; Lillas, Connie (Frontiers in Integrative Neuroscience, 2020)
The specific role of the autonomic nervous system (ANS) in emotional and behavioral regulation—particularly in relation to automatic processes—has gained increased attention in the sensory modulation literature. This mini-review summarizes current knowledge about the role of the ANS in sensory modulation, with a focus on the integrated functions of the ANS and the hypothalamic–pituitary–adrenal (HPA) axis and their measurement. Research from the past decade illustrates that sympathetic and parasympathetic interactions are more complex than previously assumed. Patterns of ANS activation vary across individuals, with distinct physiological response profiles influencing the reactivity underlying automatic behavioral responses. This review advances a deeper understanding of stress and the complex stress patterns within the ANS and HPA axis that contribute to allostatic load. We argue that using multiple physiological measurements to capture individual ANS response variation is critical for effectively treating children with Sensory Modulation Disorder and sensory differences. We consider the relative contributions of automatic versus deliberately controlled processes across large-scale neural networks in the development of sensorimotor function and their associated links with arousal patterns and sensory over- and under-responsivity.